A repertory grid-based interactive e-book approach to supporting in-field mobile learning activities in an ecology course. (2016) - Chang, Shao-Chen; Wang, Sheng-Yuan; Hwang, Gwo-Jen
Previous studies have indicated the importance of having students learning from the real-world contexts via observing and interacting with authentic learning target; in the meantime, educators have also pointed out the need of providing effective supports to help students organise knowledge acquired from both the courseware and real-world contexts. In this study, a repertory grid-based interactive e-book approach is proposed to guide students organising what they have observed in the field and what they have learned from textbooks during the field trip. An experiment has been conducted in an ecology course to evaluate the performance of the proposed approach. A total of 52 fifth graders from two classes participated in the experiment. A class of 26 students was assigned to experimental group who learned with the proposed approach. Another class with 26 students was the control group, who learned with conventional mobile learning with interactive e-books. From the experimental results, it was found that the proposed approach significantly improved the students' learning achievements and learning motivation, and decreased their cognitive load in the meantime.